DEDIKASI SUPARNI DALAM DUNIA KEPESINDHENAN DI SURAKARTA - Riza Indri Hapsari; Rusdiyantoro Rusdiyantoro (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2022)
This study explains the factors that make up Suparni as a pesindhèn in the realm of Surakarta-style karawitan. Suparni became one of the senior sindhens who still exists in his world today. Therefore, youcan solvethe problem  of Suparni's form factor into pesindhèn, namely  by using Alvin Boskof's theory of social change f.  Suparni's forming factors are divided into two, namely  internal factors   and external factors. The results of the research that has been carried out, it is known that theinternal actors in Suparni consist of  creativity, talent, as  well as traits and personalities. While external factors consist of the environment and its experience. It is these factors that have shaped Suparni as pesindhèn, even today.